1982
DOI: 10.1111/j.1943-278x.1982.tb00916.x
|View full text |Cite
|
Sign up to set email alerts
|

The Ecology of Self‐Injury: A Multivariate Approach

Abstract: In an ecological study of the distribution of self-injury in London, Canada, the authors found that self-injury occurred more frequently in the central areas of the city. Multivariate analysis revealed that living arrangements, such as high density of housing and single-person households, are closely associated with inflated rates on self-injury. Low socio-economic status is also related to self-injury but neither family status nor mobility are significant predictors. Ecological relationships such as these sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…A second line of inquiry into social isolation examines the relationship between marital status and suicide (Baller & Richardson, 2002;Gibbs, 2000;Jarvis, Ferrence, Whitehead, & Johnson, 1982;Wasserman & Stack, 1993). Aggregate suicide studies demonstrate that divorced individuals are 38% more likely to commit suicide than their married counterparts (Kposowa & D'Auria, 2010).…”
Section: Research Contextmentioning
confidence: 99%
“…A second line of inquiry into social isolation examines the relationship between marital status and suicide (Baller & Richardson, 2002;Gibbs, 2000;Jarvis, Ferrence, Whitehead, & Johnson, 1982;Wasserman & Stack, 1993). Aggregate suicide studies demonstrate that divorced individuals are 38% more likely to commit suicide than their married counterparts (Kposowa & D'Auria, 2010).…”
Section: Research Contextmentioning
confidence: 99%
“…The history of aggregate studies on attempted suicide is shorter and less productive. Regional differences in attempted suicide in the UK (10 -19), the USA (20), Canada (21,22) and Australia (23) suggest that attempted suicides are associated with poor living conditions and other forms of social deprivation. Most urban studies have found high attempted-suicide rates in city centres, with lower rates in residential suburban areas.…”
mentioning
confidence: 99%
“…The studies by Jarvis et al (22) in Canada, as well as Gunnell et al (10) and Congdon (11) in the UK are rare in having made special efforts to include all attempted-suicide admissions without any selection. These three studies show that attempted-suicide rates are most strongly in uenced by socio-economic deprivation, especially among men (11).…”
mentioning
confidence: 99%
“…All these counties are urban areas and have populations larger than 100,000. This conclusion seems to be more reasonable, because suicides are more likely to occur in urban than in The counties with the five largest suicide rates in California, based on the rural areas (Jarvis et al, 1982;Koller & Cotgrove, 1976;Morgan et al, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing need for strategies that can help public and mental health decision makers appropriately target scarce resources for suicide prevention toward those persons and places in greatest need of intervention. Suicide mapping can be a valuable tool for this task (Ashford & Lawrence, 1976;Boor, 1981;Farmer, Preston, & OBrien, 1977;Jarvis, Ferrence, Whitehead, & Johnson, 1982;Koller & Cotgrove, 1976;Lester, 1980;Miller, 1980;Moens, 1984;Morgan, Pocock, & Pottle, 1975). However, it has been difficult to choose an appropriate statistical measure that is reliable and correctly indicates the relative magnitudes of a suicide rate across relatively small geopolitical units such as counties.…”
mentioning
confidence: 99%